2020
DOI: 10.1002/slct.202000191
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Antimicrobial Evaluation of 1,3,4‐Oxadiazole/1,2,4‐Triazole‐Substituted Thiophenes

Abstract: The increasing level of antimicrobial resistance in pathogenic bacteria, together with the lack of new potential drug scaffolds in the pipeline, make the problem of infectious diseases a major public health concern. Thus, in this context, a novel series of 1,3,4-oxadiazole-substituted thiophenes (4 a-m) and 1,2,4-triazole (6 a-m) substituted thiophene derivatives were synthesized. Characterization of all the synthesized derivatives was done by various spectroscopic techniques such as 1 H NMR, 13 C NMR spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…The visualization of molecular docking study results was carried out for a series of compounds ( 3.7 , 3.9 , and 4.2 ) and methotrexate to estimate the nature of possible ligand–DHFR interactions. [ 18 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The visualization of molecular docking study results was carried out for a series of compounds ( 3.7 , 3.9 , and 4.2 ) and methotrexate to estimate the nature of possible ligand–DHFR interactions. [ 18 ]…”
Section: Resultsmentioning
confidence: 99%
“…It was found that lg IC 50 of compounds 3.9 The visualization of molecular docking study results was carried out for a series of compounds (3.7, 3.9, and 4.2) and methotrexate to estimate the nature of possible ligand-DHFR interactions. [18] The visualization of the X-ray diffraction study of the DHFR-MTX complex (Table 1, Figure 2a) reveals the nature of ligand-enzyme interactions. It was shown that the molecule of MTX forms numerous conventional hydrogen bonds that can be considered as electron-donating interactions of amino groups in 2nd and 4th position of the pteridine cycle with amino acids ASP A:27 ( The validity of the docking study can be estimated by the value of RMSD, which characterizes the degree of reliable docking probability.…”
Section: Molecular Docking and Dhfr Inhibition Assaymentioning
confidence: 99%
“…Thus, reaction with hydrazine gave the corresponding hydrazides as key intermediates that were converted into compounds 87 by reaction with carbon disulfide and into compounds 88 through a sequence involving reaction with allyl isothiocyanate and ring closure of the resulting thiosemicarbazide in alkaline conditions. [ 95 ] Compounds 87 (R = 4‐FC 6 H 4 , R 1 = H; R = 4‐ClC 6 H 4 , R 1 = H) stood out as broad‐spectrum, highly active antimicrobial agents in series of thiophene–oxadiazole hybrids (MICs between 5 and 15 μg/ml), while their counterparts 88 in the thiophene–triazole series were marginally superior in terms of overall antibacterial activity (MICs between 2 and 12 μg/ml). Among the bacterial strains, S. aureus was the most sensitive to the action of these 2‐aminothiophenes, while E. coli was the least susceptible bacteria to their activity.…”
Section: Aminothiophenes As Scaffolds For Antimicrobial Agentsmentioning
confidence: 99%
“…Thus, reaction with hydrazine gave the corresponding hydrazides as key intermediates that were converted into compounds 87 by reaction with carbon disulfide and into compounds 88 through a sequence involving reaction with allyl isothiocyanate and ring closure of the resulting thiosemicarbazide in alkaline conditions. [95] Compounds 87 The use of hydrazidones derived from cyanoacetic acid hydrazide in the Gewald synthesis has been disclosed to afford 3aminothiophenes with ketones such as cycloalkanones as the active methylene reagent, while the end product is a 2,4-diaminothiophene when the active methylene component is either malononitrile or ethyl cyanoacetate. Thus, 3-aminothiophene 89 and 2,4diaminothiophene 90 (Figure 10) were synthesized through a Gewald synthesis starting from the hydrazidone obtained from 2-cyanoacetohydrazide and 4-acetyl-N,N-ethylmethylbenzene sulfonamide and their antibacterial evaluation using the agar plate diffusion method showed that both were active against all the bacterial strains included in the test panel, with the exception of P. aeruginosa.…”
Section: Antimicrobial Agents With An Unsubstituted 2-aminothiophene ...mentioning
confidence: 99%
“…[39] Based on the inhibitory concentration a set of 26 poly substituted 2-amino thiophene derivatives were selected for the study from the literature. [40] PADEL software was used to calculate the 2D Descriptors. Currently, the software calculates 1875 descriptors and 12 different types of fingerprints.…”
Section: Introductionmentioning
confidence: 99%